The presence of outer arm fucose residues on the N-glycans of tissue inhibitor of metalloproteinases-1 reduces its activity. - Kim, H; Saldova, R; Park, J; Lee, Y; Harvey, D; Wormald, M; Wynne, K; Elia, G; Kim, H; Rudd, P; Lee, S (2013)
Tissue inhibitor of metalloproteinases-1 (TIMP-1) inhibits matrix metalloproteinases (MMPs) by binding at a 1:1 stoichiometry. Here we have shown the involvement of N-glycosylation in the MMP inhibitory ability of TIMP-1. TIMP-1, purified from HEK 293 cells overexpressing TIMP-1 (293 TIMP-1), showed less binding and inhibitory abilities to MMPs than TIMP-1 purified from fibroblasts or SF9 insect cells infected with TIMP-1 baculovirus. Following deglycosylation of TIMP-1, all forms of TIMP-1 showed similar levels of MMP binding and inhibition, suggesting that glycosylation is involved in the regulation of these TIMP-1 activities. Analysis of the N-glycan structures showed that SF9 TIMP-1 has the simplest N-glycan structures, followed by fibroblast TIMP-1 and 293 TIMP-1, in order of increasing complexity in their N-glycan structures. Further analyses showed that cleavage of outer arm fucose residues from the N-glycans of 293 TIMP-1 or knockdown of both FUT4 and FUT7 (which encode for fucosyltransferases that add outer arm fucose residues to N-glycans) enhanced the MMP-binding and catalytic abilities of 293 TIMP-1, bringing them up to the levels of the other TIMP-1. These results demonstrate that the ability of TIMP-1 to inhibit MMPs is at least in part regulated by outer arm fucosylation of its N-glycans.